Influencia de la calidad de vida en el rendimiento académico de los estudiantes del I ciclo de la Facultad de Ingeniería de Sistemas y Medicina Humana de la Universidad Nacional de San Martin Tarapoto semestre 2015-I - Villa Díaz, Clarita Elizabeth (2015)
This research aims to determine the influence of the quality of life in the academic performance of students in the first cycle of the Faculty of Systems Engineering and Faculty of Human Medicine during the academic semester 2015-I National University San Martin-Tarapoto, comparative quantitative correlational study with prospective data collection .Cuya population was 94 students who completed the first half cycle 2015-I, corresponding to 47 students for each faculty, the method used was the survey by applying the questionnaire WHOQOL BREF. The results were: Students are male with 89% and 55% FISI FMH, 80% aged 16-19 for both powers. Quality of Life very good, with a higher proportion em FISI 34.04% (16), while for the FMH was 21.28% (10). The achievement for FISI and FMH was fair, being higher in the FISI with 74.47% (35) compared to 59.57% (28) to the WFH. In conclusion there is significant influence on the physical dimensions and environmental x2 = x2 = 14,034 to 14,020 students and FISI for FMH had significant influence only in the physical dimension x2 = 14.370 FMH being who has the greatest influence on the quality of life academic performance 10.486yp = x2 = 0.033.